2009
DOI: 10.1021/ma900414h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Deformation Mechanisms and Tensile Properties of Tetrafunctional Multigraft Copolymers

Abstract: Morphology and deformation mechanisms and tensile properties of tetrafunctional multigraft (MG) polystrene-g-polyisoprene (PS-g-PI) copolymers were investigated dependent on PS volume fraction and number of branch points. The combination of various methods such as TEM, real time synchrotron SAXS, rheo-optical FTIR, and tensile tests provides comprehensive information at different dimension levels. TEM and SAXS studies revealed that the number of branch points has no obvious influence on the microphase-separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…Again, the optimal DAEMA content seems to be in the 25-45% range, yielding copolymers with T g values 10-30 C below ambient temperature. The three samples with intermediate DAEMA content (30,35, and 40%) all showed steep stress increases at low strain, ductile yielding, and elastoplastic deformation to large failure strains (>500%). As DAEMA content increases, the failure strain decreases, but the failure tensile stress increases.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Again, the optimal DAEMA content seems to be in the 25-45% range, yielding copolymers with T g values 10-30 C below ambient temperature. The three samples with intermediate DAEMA content (30,35, and 40%) all showed steep stress increases at low strain, ductile yielding, and elastoplastic deformation to large failure strains (>500%). As DAEMA content increases, the failure strain decreases, but the failure tensile stress increases.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…These gra copolymers consist of either so backbone and hard side chains, or rigid backbone and rubbery side chains, which can be prepared by various graing chemistry strategies. 25,[33][34][35][36] For instance, polyisoprene-g-polystyrene (PI-g-PS) has been synthesized via anionic polymerization as gra copolymer-based TPE. 34,35 The Kramer and Bazan groups developed a gra copolymer by graing so n-butyl acrylate from rigid polyethylene copolymer backbone through ATRP.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation
“…Structure-property relationship of these graft copolymers was elucidated by characterizing morphology [76,77] and mechanical properties [78][79][80] of grafted polymers with different compositions (14-23 vol% of PS) and architectures (trifunctional, tetrafunctional, and hexafunctional junction points). From their research, multigraft polymers with tetrafunctional junction points showed 1550% strain at break which is 500% higher than that for the commercial product Kraton 1102.…”
Section: Graft Copolymer-type Tpesmentioning
confidence: 99%
“…13 However, to date, there is almost no one polar monomer, which could be used as the monomer in the anionic polymerization in industrial scale, also including the commonly used methyl methacrylate (MMA). Due to too more side reactions are likely to occur during the anionic polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%